Howard Watkins' Retirement from Fresno-Merced Counties Legal Services Dinner at Yen Ching Restaurant - Watkins, Howard::::::::: (1985)
On left: Laurie Leifer, Michael Coburn, Herbert Levy, Dora Gonzales and Lloyd Gonzales; Right: guest, Christine Watkins, Howard Watkins and guest Howard now clean shaven-no beard or mustache